Oxidação com Cu-Fau e CO2 como oxidante em processo contínuo e com modulação CH4-CO2 - Carvalho, Yasmin Oliveira (2024)
The direct oxidation of methane to methanol has been a long-standing challenge in heterogeneous catalysis, with limited methanol production during each catalytic cycle. An alternative option would be to implement a continuous gas-phase process with high productivity, which for safety reasons requires high control over the use of O2. In the present work, it was possible to obtain a continuous process for the isothermal conversion of methane to methanol at high temperature (350-400ºC) using CuFAU and suppressing the methanol extraction step with steam. By replacing O2 with CO2 as oxidant and removing water vapor from the process, the active phase Z-CuOH.HOCu-Z becomes Z-Cu3O3-Z. Z-Cu3O3-Z species are reduced by CH4 and reoxidized by CO2. Modulation tests with CH4 and CO2 revealed that the amount of oxygen available for the reaction is much greater than that present in the active phase Z-Cu3O3-Z. It was found that under the reaction conditions, when CO2 is fed to the reactor, part of it is adsorbed on the zeolite, which is used in the reoxidation of the active species when reduced by methane. Thus, by feeding the reactor only with CH4 at 7 bar, methanol could be formed and desorbed at a temperature of 400°C for a long time (> 3 h), with an average rate of 162.6 µmolmethanol.(gcat.h)-1 . The results show the possibility of continuous methanol formation in the absence of O2, with yields of the order of those obtained in the looping approach. Therefore, this process seems to be a step forward towards the possible commercialization of the direct conversion of methane to methanol.